‘Refugees are streaming into Europe’: An image-schema analysis of the Syrian Refugee crisis in the Spanish and British press - Romano, Manuela (Complutense Journal of English Studies, 2019)
By analysing the combination of an apparently neutral water metaphor, ‘flujo de refugiados / (in)migrantes’ and ‘flow of refugees / (im)migrants’, with very specific image schemas, in El País and The Guardian from 2015 to 2016, when the Syrian refugee crisis was at its peak, this study aims at uncovering the conceptualization of the refugees in two European host countries. To this aim, the study contributes to the field of anti-immigration discourse by presenting a comprehensive qualitative analysis of all the image schemas identified in the data (force, path, up-down, container, and balance); a cross-linguistic and corpus-based, quantitative analysis of the different schemas used in the newspapers; and a study based on the left-wing press, intuitively considered to have a more pro-immigration orientation. In short, the analysis reveals how, these highly covert preconceptual structures, used as powerful ideological tools, help to shape public opinion by projecting a very clear refugees as danger frame.